Pengaruh Besaran Premi Terhadap Minat Menjadi Nasabah Asuransi di PT. Asuransi Tugu Pratama Indonesia - Muhammad Farhan Abdillah Lubis; Rahmayati Rahmayati (-, 2022)
This study was conducted with the aim of analyzing the effect of premium on interest in becoming an insurance customer at PT. Tugu Pratama Indonesia Insurance in Medan City. The importance of this research is because there are many insurance companies that compete with each other with intense competition with the same premium amount. A total of 60 respondents is the number of samples used in analyzing data using T test, F test, validity test, reliability test and R2 test. The results of this study state that the premium amount has a positive and significant effect on the interest in becoming an insurance customer tested at PT. Tugu Pratama Indonesia Insurance.